The multiple identities of sustainability. Issue 3 (13th July 2015) - Ratiu, Catalin; Anderson, Beverlee B.
Abstract : Purpose: – Sustainability is one of the most complex composite constructs to have emerged in the last decades. Having a clear understanding of its meanings is critical as actions based on these understandings impact all walks of life. The purpose of this paper is to track the conceptualizations and measurements of sustainable development in the areas of government, business, education, and the trades. Design/methodology/approach: – Through a multi-method design, the authors explore what stakeholders in these groups value in sustainability by observing where they develop initiatives, invest funds, and report progress. Findings: – What emerges is a picture of diverse views and multiple identities, driven by distinct logics and motives. Originality/value: – Based on these findings, the authors propose that, instead of reconciling these diverse perspectives, the authors might focus on constructing shared understandings around critical values.